Origin and evolution of emotional education - Machado Pérez, Yumary (2022)
At present, emotional education has become one of the great challenges of the 21st century school, since it must educate students both academically and emotionally. This has its origins in the different theories of emotional intelligence. The present article aims to systematize the origin and evaluation of emotional education, for this a synthesis and analysis of different theories of emotional intelligence was developed considering the authors Salovey and Mayer, Bar-On, Goleman, Bisquerra and Fernández-Berrocal and Extremera. This allowed us to know the evolution and current state of emotional intelligence theories and their link and applicability in the educational field. For this, we worked with the documentary research methodology following the hermeneutical method.